Intestinal Microbiome Profiles in Broiler Chickens Raised with Different Probiotic Strains - da Silva, Julia Marixara Sousa; Almeida, Ana Maria De Souza; Borsanelli, Ana Carolina; de Athayde, Flávia Regina Florencio [UNESP]; Nascente, Eduardo de Paula; Batista, João Marcos Monteiro; Gouveia, Alison Batista Vieira Silva; Stringhini, José Henrique; Leandro, Nadja Susana Mogyca; Café, Marcos Barcellos (MDPI, 2024)
The composition of the intestinal microbiota can influence the metabolism and overall functioning of avian organisms. Therefore, the objective of this study was to evaluate the effect of three different probiotics and an antibiotic on the microbiomes of 1.400 male Cobb® broiler raised for 42 days. The experiment was conducted with the following treatments: positive control diet (basal diet + antibiotic); negative control diet (basal diet without antibiotic and without probiotic); basal diet + Normal Avian Gut Flora (NAGF); basal diet + multiple colonizing strain probiotics (MCSPs); and basal diet + non-colonizing single strain probiotics (NCSSPs). The antibiotic (enramycin—antibiotic growth promoter) and probiotics were administered orally during all experiment (1 to 42 days), mixed with broiler feed. To determine the composition of the microbiota, five samples of ileal digesta were collected from 42-day-old chickens of each experimental group. The alpha and beta diversity of the ileal microbiota showed differences between the groups. MCSPs presented greater richness and uniformity compared to the positive control, negative control, and NCSSPs treatments, while the negative control exhibited greater homogeneity among samples than NCSSPs. MCSPs also showed a higher abundance of the genus Enterococcus. There were differences between the groups for low-abundance taxa (<0.5%), with NAGF showing higher levels of Delftia, Brevibacterium, and Bulleidia. In contrast, NCSSPs had a higher abundance of Ochrobactrum, Rhodoplanes, and Nitrospira. It was concluded that the treatments analyzed in this study induced modulations in the ileal microbiota of the chickens examined.
Keywords: alternatives to antibiotics; intestinal health; microbiome; modulation; poultry farming